2009
DOI: 10.3109/00365520903401967
|View full text |Cite
|
Sign up to set email alerts
|

Stressful psychosocial factors and symptoms of gastroesophageal reflux disease: a population-based study in Norway

Abstract: This population-based study reveals a link between stressful psychosocial factors, including job strain, and GERD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…Several studies have documented significant variations in morbidity of internalizing disorders and stress exposure among different ethnic groups . Significant relationships between psychosocial factors and the development of a broad array of gastrointestinal disorders had been reported . A recent animal study demonstrated that acute stress can increase esophageal permeability, which shed light on the patho‐physiological mechanism of GERD .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented significant variations in morbidity of internalizing disorders and stress exposure among different ethnic groups . Significant relationships between psychosocial factors and the development of a broad array of gastrointestinal disorders had been reported . A recent animal study demonstrated that acute stress can increase esophageal permeability, which shed light on the patho‐physiological mechanism of GERD .…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory stress has been found to increase the perception of intraluminal acid stimuli and induced stress, anxiety, anger in GERD patients rather than normal control. [25] Stressful psychosocial factors can induce GERD, [26] and stress may also induce bipolar disorder in patients genetically prone to developing bipolar disorder. [27], [28] Psychological stress also may activate inflammatory responses in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research indicates that the severity of GORD symptoms varies substantially across patients, and evidence suggests that psychological factors are likely to contribute to this variability. For instance, it has been shown that individuals experiencing psychological distress, such as anxiety or depression, are more likely to report oesophageal symptoms and to be diagnosed with GORD (Jansson et al., ; Shapiro et al., ; Kessing et al., ). Another study showed that catastrophic thinking is associated with more intense pain among patients with painful gastrointestinal problems, including GORD (Drossman et al., ).…”
Section: Introductionmentioning
confidence: 99%